Farmers’s Perception of Soil Fertility Management in Semi-Arid Regions an Empirical Analysis: a Case of Andhra Pradesh. - Reddy, B. Suresh (2010)
Soil Fertility Management (SFM) is a key to sustainable livelihoods of rural people in semi-arid tropics in India. Based on the field work done in Andhra Pradesh state, this paper highlights the diverse soil fertility management practices being followed by the farmers of all size classes. Except the practice of application of chemical fertilizers all other practices are organic in nature and have no negative impact on soil health or environment. Farmers perceived that farm yard manure application is best to their long term soil health. Based on the empirical evidence this study argues for the strong policy support to all the SFM practices but just not chemical fertilizers alone.